2015
DOI: 10.1159/000369812
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Disease Is Less Prevalent in Amyotrophic Lateral Sclerosis

Abstract: Background/Aims: Recent studies suggest that antecedent disease could impact the pathophysiology of the motoneuron disease Amyotrophic Lateral Sclerosis (ALS). We performed a case-control study to examine the prevalence of 11 antecedent diseases in ALS. Methods: Prevalence of antecedent disease in a 1,288 patient ALS population (Emory University ALS Clinic, Atlanta, Ga., USA) is compared to an age, gender, and geography-matched 7,561 subject control population using a statistical odds ratio (OR) with 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 23 publications
3
58
1
1
Order By: Relevance
“…While there is evidence suggesting that ALS patients may be less likely than the general population to have cardiovascular disease and cardiovascular risk factors [17], no such difference was observed in our population between prevalent ALS patients and controls. The significantly lower prevalence of CKD among ALS patients compared to controls in our study is similar to a previous study, which found an odds ratio of 0.32 (95% CI 0.18-0.57) for ALS patients compared to age- and sex-matched controls [18]. A low CKD prevalence is also consistent with ALS patients' significantly lower BMI.…”
Section: Discussionsupporting
confidence: 89%
“…While there is evidence suggesting that ALS patients may be less likely than the general population to have cardiovascular disease and cardiovascular risk factors [17], no such difference was observed in our population between prevalent ALS patients and controls. The significantly lower prevalence of CKD among ALS patients compared to controls in our study is similar to a previous study, which found an odds ratio of 0.32 (95% CI 0.18-0.57) for ALS patients compared to age- and sex-matched controls [18]. A low CKD prevalence is also consistent with ALS patients' significantly lower BMI.…”
Section: Discussionsupporting
confidence: 89%
“…On a similar note, a recent study of non-familial clinical ALS patients showed that antecedent disease is substantially less prevalent among ALS patients, including metabolic disturbances like diabetes, obesity and thyroid disease, which suggests the possibility of neuroprotection—either “other disease is protective of ALS” or “ALS is protective of other disease” [32]. In fact, the pathophysiological process oscillations seen in models examining the SOD1 G93A underlying pathophysiology, suggest the possibility of “hypervigilant regulation” (in control theory a too-high feedback gain).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pathophysiological process oscillations seen in models examining the SOD1 G93A underlying pathophysiology, suggest the possibility of “hypervigilant regulation” (in control theory a too-high feedback gain). Regulatory delays combined with the too-high feedback gain(s) of hypervigilant regulation, could ultimately result in system instabilities identified in the SOD1 G93A model that dramatically impact the onset and progression of ALS [3234]. In short, genetic differences underlying cellular and systemic regulation could result in different ALS phenotypes, both in transgenic mouse models and in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, autonomic [7, 8], blood pressure regulation [3841], and even the potential role of antecedent disease and its affect on homeostasis [e.g. 42], has been previously discussed in the clinical literature. In summary, the widespread identification of overlapping pathological features quantified in this study lends credence to the hypothesis that ALS, FTD, as well as other neuropathologies, could potentially share interrelating etiologies [1, 2, 9], which may represent a larger motor-neurodegenerative-cognitive neuropathological continuum.…”
Section: Discussionmentioning
confidence: 99%